Targeted analysis of eicosanoids derived from cytochrome P450 pathway by high‐resolution multiple‐reaction monitoring mass spectrometry. (13th June 2021) - Acunha, Tanize; Nardini, Viviani; Peti, Ana Paula Ferranti; Prado, Morgana Kelly Borges; Moraes, Luiz Alberto Beraldo; Faccioli, Lúcia Helena
Abstract: Cytochrome P450 (CYP450) pathway is one of the critical enzymatic via eicosanoid biosynthesis. Nevertheless, their metabolites are far less explored. This pathway plays a crucial role in converting arachidonic acid to hydroxyeicosatetraenoic (HETEs), epoxyeicosatrienoic (EETs), dihydroxyeicosatetraenoic acids (DiHETEs), and dihydroxyeicosatrienoic acids (DiHETrEs), which mediate several physiological and pathological functions. However, CYP450‐derived eicosanoids are structurally complex, making those analyses a challenge in lipidomics studies. Herein, a high‐resolution multiple‐reaction monitoring (MRM HR ) method has been proposed as a powerful tool for the simultaneous analysis of CYP450‐eicosanoids on different biological samples. The developed liquid chromatography (LC)‐MRM HR method was partially validated according to the Food and Drug Administration (FDA) criteria, demonstrating adequate specificity, linearity, precision, and accuracy. Besides, several biological samples were analyzed to guarantee the feasibility of the method. The proposed strategy may improve the understanding of CYP450‐derived eicosanoids in biological systems, which could be fundamental to reveal new aspects of those in physiologic and pathologic conditions.